Pleasure - Seeking Personality Reflected In Theodore Dreiser's Sister Carrie (2005): A Psychoanalytic Approach - Nurussa'adah, Fathiana; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
The aim of this research is to describe 'Sister Carrie' novel based on structural elements of the novel and to analyze how pleasure-seeking personality is reflected in Theodore Dreiser's Sister Carrie by using psychoanalytic approach. This research is qualitative research and technique of analyzing data is descriptive analysis. The techniques of collecting data are (1) Reading the novel repeatedly and underlying the important data. (2) Exploring the main data of character that will be analyzed. (3) Identifying a particular part that is important and relevant for the analysis. (4) Making note both primary and secondary data, and (5) Classifying the data into some categories. Based on the psychoanalytic theory, it can be concluded that the personality of major character in 'Sister Carrie' is classified as pleasure-seeking personality. Carrie's Id is more dominant than Ego and superego. Carrie's personality is caused by economic situation.